The Importance of Using a Web-Based Learning Model to Prevent the Spread of COVID 19 - Wirani, Nasrah; Manurung, Asrar Aspia (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2020)
Online learning is known that is learning that is connected to a computer or android network. In addition to Online there are also many learning using the internet such as WEB-based learning, Hybrid Learning and E-Learning. The author's objectives are (1) knowing WEB-based learning models, (2) to find out the Implementation of WEB-Based Learning, (3) prevention of the spread of COVID-19. The research used is Quantitative Research and using WEB-based learning models. Therefore it is very important WEB learning model to prevent the spread of COVID - 19. From the results that can be seen in using this learning model, students sometimes find it difficult to understand the explanation given by educators. Due to internet limitations or android usage. So it is recommended for students with the use of online learning models students can reduce activities outside the home and can help reduce the distribution chain of COVID-19.Keywords: WEB Based, Implementation, COVID prevention - 19